CAPITALISM: SOME THEORETICAL RECONSIDERATIONS - David Laibman (World Review of Political Economy, 2010)
Attempts to understand the current economic crisis, the present stage of world capitalist development and the nature and role of socialist forces will be inconclusive and non-convergent, unless they are based on a rigorous foundation in the theory of capitalist surplus extraction in its pure form, and of the stadial (stages-based) nature of capitalist evolution. Capitalist exploitation rests upon three pillars: differential property ownership, workplace hierarchy and coercion, and existence of a social upper class; these pillars in turn require for their support the market, developed industrial production, and the modern state. Stadial development proceeds through four stages, based on the distinction between diffusion and accumulation, which in turn operate internally and externally in relation to the nation-state. Full capitalist development, in light of this model, is much less ubiquitous in today's world than is usually believed, and much less close to complete stadial fulfillment. Socialist forces must confront these realities in order best to build conditions for socialist construction and social transformation.